Pediatric postmortem CT angiography: validation of vascular access for PMCT angiography in stillbirths, babies and toddlers - Bruch, Gina Maria; Hofer, Peter; Ferraz da Silva, L. F.; Pires-Davidson, J. R.; Bento dos Santos, G. A.; Fischer, Florina Tabea (Forensic science, medicine, and pathology, 2023)
Purpose  The use of angiography in postmortem CT angiography (PMCTA) has several advantages. In adults, femoral vascular access is well established. Due to the small and specific anatomy in fetuses and infants, the technique has to be adapted, especially regarding the vascular access. The aim of this study was to evaluate vascular access for pediatric PMCTA (pedPMCTA). Materials and Methods  Ten pedPMCTAs were performed in stillbirths, babies, and one toddler. A femoral approach by cannulation of the femoral artery and vein, an umbilical approach by cannulation of the umbilical vessels, and an intraosseous approach by an intraosseous needle were evaluated by handling and resulting imaging. - Results  The insertion of a cannula with a size of 18-20 G in the femoral vessels was possible in babies. An umbilical access with peripheral venous cannulas with a size of 14-20 G was feasible in stillbirths and newborns. An intraosseous access is advisable as equal alternative to umbilical and in cases where a femoral access is not possible. The most significant problem with the vascular access is the extravasation of contrast media, but this can be reduced significantly with practice. - Conclusion  When performing pedPMCTA, an umbilical vascular access is recommended if an umbilical cord with open vessels is still present. Otherwise, a bone marrow access should be preferred in the presence of an arteriovenous shunt or if only the venous system needs to be shown. If that is not the case, the femoral access with the possibility to separate venous and arterial scan should be used.
Gesehen am 15.07.2024